Kratom (Mitragyna speciosa): User demographics, use patterns, and implications for the opioid epidemic. (1st March 2020) - Garcia-Romeu, Albert; Cox, David J.; Smith, Kirsten E.; Dunn, Kelly E.; Griffiths, Roland R.
Highlights: Kratom is a Southeast Asian plant with opioid-receptor mediated effects. Kratom has recently emerged as a substance of abuse, with limited available data. Kratom is being used by White, middle-aged Americans for pain, anxiety, depression. Users also report using kratom to decrease opioid use, withdrawal, and craving. Additional research on kratom epidemiology and pharmacology is necessary. Abstract: Background: Kratom, a Southeast Asian plant with opioid-receptor mediated effects, has emerged as a potential substance of abuse, with limited data on its use and effects. This study characterized kratom user demographics, use patterns, and perceived drug effects. Methods: A cross-sectional, anonymous online survey was conducted between January and December 2017. Results: 2, 798 kratom users – mean age 40 (SD = 12); predominantly White (90 %), female (61 %), and located in the US (97 %) – completed the survey. Kratom was primarily taken orally in doses of 1−3 g (49 %), with daily use (59 %) being most common. Kratom was used for pain (91 %), anxiety (67 %), and depression (65 %), with high ratings of effectiveness. 1, 144 (41 %) used kratom to stop or reduce prescription or illicit opioid use, citing decreased opioid withdrawal and craving related to kratom use, with 411 reporting >1-year continuous abstinence from opioids attributed to kratom use. Roughly one-third of respondents reported adverse effects of kratom, largely rated as mild in severity and lasting ≤24 h. Seventeen participants (0.6 %) sought treatment for adverse effects. Fifty-six individuals (2 %) met DSM-5 criteria for a past-year moderate or severe kratom-related substance use disorder (SUD). When asked how troubled they felt regarding their kratom use, the mean (SD) rating was 3.2 (9.8) on a scale from 0 to 100. Conclusion: Kratom is used among White, middle-aged Americans for symptoms of pain, anxiety, depression, and opioid withdrawal. Although regular use was typical, kratom-related SUD and serious adverse effects were uncommon. Additional research on kratom epidemiology and pharmacology is imperative in light of the present opioid epidemic.